Thomas Fink entrevista Lakshmi Bandlamudi: Difference, Dialogue and Development: a Bakhtinian World - Lima, Anselmo; Ruffini, Mirian (Bakhtiniana. Revista de Estudos do Discurso, 2019)
Entrevista original publicada em: https://dichtungyammer.wordpress.com/2017/03/19/exchange-on-lakshmi-bandlamudis-difference-dialogue-and-development-a-bakhtinian-world-routledge-2015/